Poder, mídia e discurso na "canonização" do cangaceiro Jararaca - Rosado, Cid Augusto da Escóssia (2021)
This dissertation approaches utterances related to the bandit José Leite de Santana, known as Jararaca, in which, after being imprisoned and executed by the policemen, in the episode of the frustrated attack to Mossoró-RN by the Lampião’s group, he started to be seen as a miracle-worker, in which overrided the other Mossoroense warriors in the place’s memory. Those are events that are perpetuated in time and space, interconnected by tradition of resistance to the bandits and by the leitmotif of communication and the movement of power in the society. The disruptions which allowed such phenomena motivated this work, whose goal is to analyze discourses that produce meaning regarding how the heroes of the city were relegated to the anonymity and José Leite de Santana transformed into a folk saint. Thus, this research has a qualitative nature inserted into the Undisciplined Applied Linguistics (MOITA LOPES, 2006), with documentary analysis centered in a corpus made by journalistic reports conveyed in 1927, 1977 and 2017. The theoretical discussion is underpinned on language studies, with Foucault (1987, 1988, 2004, 2005, 2006, 2007a, 2007b e 2013) from which concepts and procedures related to the Discourse Analysis method are extracted, as well as the notions of power, resistance, and the spectacle of the scaffold; it does involves social and historical theorizing, invoking Hobsbawm (2010), Fernandes (2009), Silva (2007b), Pericás (2010) and Falcão (2013) to understand the banditry in the Northeast; and, finally, aims, in the communication field, especially in Sousa (2004), Traquina (2001, 2005), Thompson (2004), Charaudeau (2006), Wolf (2003) and Kellner (2001), clues to interpret the role of the media in the transformation of the criminal into a miracle-worker. The conclusion reached is that the Jararaca which lives in the imagination of Mossoró-RN is not that man who was captured and killed, but it is an idealized figure and “canonized” in the set of discourses produced about him.